A numerical study on the responses of coastal water quality to river runoff after heavy rainfall in the case of a complex coastline with two artificial islands - Wang, Gang; Feng, Xin; Zhang, Jiabo; Huang, Zhe; Bai, Yuchuan; Song, Wei; Xu, Haijue (Frontiers in Marine Science, 2023)
Heavy rainfall causes large volumes of freshwater and nutrient salts to flow from rivers into the sea. This leads to major changes in the ecological environment of estuarine waters in a short period of time. The responses of the estuarine hydro-environment become more complex with the concentrated construction of artificial structures, which is a major cause of marine ecological disasters. This paper considers the Tang Estuary in Qinhuangdao, where artificial structures (e.g., ports, artificial islands, and bridges) are concentrated, as a prototype with the weak tidal dynamic environment. A nested prototype of hydrodynamics and water quality was established using a Delft3D model, with coupled waves and flows. The model was used to simulate the spatial and ephemeral characteristics of the short-term responses of ecological environmental factors, such as dissolved inorganic nitrogen (DIN), nitrate-nitrogen (i.e., NO3-N), ammonium-nitrogen (NH4-N), and orthophosphate (i.e., PO4-P), to an episode of heavy rainfall in August 2022. The results showed that concentrations of DIN and NO3-N in the source areas remain high after the flooding process. The concentration recovered to normal values approximately 5.5 days after the flooding process. In contrast, NH4-N and PO4-P showed a response with ephemeral correspondence with the flooding process, and concentration recovery took only approximately 1 day. This paper proposes two short-term response modes of pollutant diffusion, which provide help in exploring the role of hydro-environmental changes in offshore algal hazards and the effect of permeable buildings on pollutant dispersion. This additionally provides possibilities with the forecasting of red tide and green tide, and for their prevention in the future.